An overview of the supply chain management of Malaysian vegetable and fruit industries focusing on channel of distribution - Man, Norsida; Mohd Nawi, Nolila; Ismail, Mohd Mansor (Federal Agricultural Marketing Authority (FAMA), 2009)
The paper delineates three fundamental characteristics of the local supply chain for vegetables and fruits in Malaysia where the marketing channels are still traditionally driven from the wholesalers’ perspectives. Produce is procured from farmers by wholesalers and then channelled to the hypermarkets and retailers. Most of the produce attributes are lacking in terms of quality, packaging, Good Agriculture Practices (GAP), traceability and safety characteristics. Most producers do not grade or pack their products and most of the production and marketing practices in the current supply chain are still traditional practices with only minor adoption of modern marketing practices being applied. This study indicates that production contract is not being practised. However, transactions on marketing or supply contracts do exist in the supply chain system. However, only a small number of farmers are involved in marketing contracts. The current system still relies on the old system of procurement and supply practices. The current supply chain management lacks attributes, such as the issues of consumer packaging, branding, and the promotion of organic farming towards sustainable agriculture. Thus, the involvement of government agencies and private sectors is essential in the promotion of production contracts to farmers.